The Rate of Women Having a Third Child and Preference of Son in Present Day Vietnamese Families - Binh, Nguyen Thanh (Mediterranean Journal of Social Sciences, 2012)
Vietnam has been implementing the policy of fertility decline through the population program, fertility health careincluding family planning. Small household size is now encouraged. Together with services of fertility health care, family planningprovided, a lot of popularizing, propagandizing activities for changing behaviors have been organized in order to equip coupleswith knowledge and encourage them to carry out the target of family planning. We have of course obtained some certainsuccess1, however there still exists the problem of couples giving birth to a third child, especially in some geographic regions,this rate tends to increase. One of the most important reasons for giving birth to a third child arise from the need of Vietnamesefamilies to have at least one son. Because the son is responsible for caring for old parents, ancestor worship, continuity thelineage, etc.